PERAN GURU MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK KELAS IV MADRASAH IBTIDAIYAH - Aslina Aslina; Asyruni Multahada; Rona Rona (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2025)
This study employed a qualitative approach and a descriptive approach. Data collection techniques included interviews, observation, and documentation. Data analysis techniques included data collection, data reduction, data display/presentation, and verification of conclusions. The data validity was verified using triangulation and member checking. The results of this study indicate that: 1) The role of teachers in implementing religious character education for students through religious activities is as follows: a) Teachers as guides, educating students from an early age to develop the habit of respecting others and smiling at each other; b) Teachers as demonstrators, demonstrating the procedures for ablution and prayer. They fully supervise and directly practice during congregational prayer; c) Teachers as educators, playing a crucial role in the Quran memorization program; d) Teachers as evaluators and motivators, evaluating each lesson to determine the success or shortcomings of the learning process; 2) Inhibiting factors that influence student character development include diverse student backgrounds, lack of awareness of school regulations, and the student's social environment. The better students understand themselves, the easier it is for teachers to help guide them in understanding the lesson. Conversely, the better a teacher's understanding of student characteristics, the better their classroom management. Therefore, understanding student character positively impacts both the students themselves and the teacher.